Price Pressures on UK Real Rates: An Empirical Investigation - Zinna, Gabriele (Review of Finance, 2016)
Abstract We assess the impact of institutional investors’ demand for gilts on UK real rates by structurally estimating the model of Vayanos and Vila (2009). We therefore include those investors believed to display inelastic demand for gilts and preferences for longer-term maturities. The estimated model fits the term structure of real rates well, and strongly supports our choice of institutional investors. These investors’ demand contributed to the decline in medium- to longer-term real rates by compressing bond risk premia. However, the price impact varied across investors and over time, and was only partly attenuated by increased supply.